(3GdbGehS GdeMjWs - (3GdTjQGRj GdajQhR BHGOj, CHh WGgQ, GdajQhR BHGOj, eMeO Hf jYbhH Hf eMeO Hf EHQGgje, J (B817(3g` (B1415(3es
(3ChdgG (B:s
(3ChdgG(B: (3hTGaJg abdb GVWQGHG TGA Ch CHj hddg UHGHI ef GdNdaGA GdMfaG hGdedhc GdYXeG JbHdhG aj GYWGa GdaVd hGYLHhG HGdefWb GdaUds
(3BNQgG (B:s
(3BNQgG(B: (3cGdNfPY HGdPGd, GdNGfY GdeQHH GdaGLQ hbO NfY cefY hGdNfYI GdaLQI hGdQjHI hGdecGf GdNGdj hdbjJg HNfYI hcUHhQ GdZGOQ GdPj jMjO Yfc hHGdVes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 146s
(3cTa GdXfhf, L (B2: 1306s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs